2010
DOI: 10.1359/jbmr.090704
|View full text |Cite
|
Sign up to set email alerts
|

Potential mediators of the mortality reduction with zoledronic acid after hip fracture

Abstract: Zoledronic acid reduces the risk of death by 28% after hip fracture, but the mechanisms are not known. This exploratory analysis sought to identify potential pathways for the reduction in mortality with zoledronic acid after hip fracture. This was a retrospective analysis of a randomized, controlled trial. Patients with recent hip fracture (n = 2111) were treated with zoledronic acid or placebo infusion yearly, as well as calcium and vitamin D supplementation. Causes of death were adjudicated by a blinded cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 29 publications
6
118
0
4
Order By: Relevance
“…According to Kanis and colleagues, (17) 17% to 32% of deaths (depending on age) after hip fracture were causally related to the fracture. In the zoledronic acid study by Colon-Emeric and colleagues, (18) subsequent fractures were significantly associated with death (HR ¼ 1.72, 95% CI 1.17-2.51) but explained only 8% of the zoledronic acid effect. Zoledronic acid also may have an effect on cardiovascular events and pneumonia, (18) and fracture prevention seems to explain only a minor proportion of the mortality reduction.…”
Section: Discussionmentioning
confidence: 97%
“…According to Kanis and colleagues, (17) 17% to 32% of deaths (depending on age) after hip fracture were causally related to the fracture. In the zoledronic acid study by Colon-Emeric and colleagues, (18) subsequent fractures were significantly associated with death (HR ¼ 1.72, 95% CI 1.17-2.51) but explained only 8% of the zoledronic acid effect. Zoledronic acid also may have an effect on cardiovascular events and pneumonia, (18) and fracture prevention seems to explain only a minor proportion of the mortality reduction.…”
Section: Discussionmentioning
confidence: 97%
“…31 An analysis of subgroups revealed that nursing home residents and those with significant cognitive impairment did not gain a mortality benefit from zoledronic acid. 32 The number of hospitalisations for adverse drug reactions may be increasing in Australia, particularly in older patients. A Western Australian study reported that the number of adverse drug reactions from 1981 to 2002 increased tenfold for men and sevenfold for women over the age of 80 years.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…6 The mechanisms responsible for mortality reduction in patients treated with zoledronic acid remain unclear, but may be related to an effect on reducing cardiovascular events and pneumonia. 7 If treatment was deferred for two weeks after the fracture, the improvements in bone mineral density and reductions in mortality and re-fracture rate were greater. 8 …”
Section: Efficacymentioning
confidence: 99%